Self-heating of viscous dampers under short- & long-duration loads: Experimental observations and numerical simulations. (February 2023) - Lak, Hassan; Zahrai, Seyed Mehdi
Abstract: Similar to other energy dissipating devices, fluid viscous damper converts its input kinetic energy to heat which in turn results in temperature rise of the device. Damper self-heating may result in excessive internal pressure due to the thermal expansion of the internal fluid. Moreover, the elevated temperature might have a detrimental effect on the sealing system of the damper. In this study, two full-scale viscous dampers are tested under short- and long-duration loading protocols. A thermal camera is used to monitor temperature rise during different loads. Based on the tests of this study, the temperature rise of the considered dampers can be neglected in the case of short-duration seismic loads, but the self-heating can be significant during long-duration loading. A numerical modeling technique is also proposed by which thermal behavior of fluid viscous dampers can be thoroughly examined. Numerical simulations are able to estimate temperature of internal and external components of the damper considering different heat transfer mechanisms. Validity of the numerical results are investigated by comparing them to the results from thermal camera. Finally, energy-temperature curves are developed to estimate thermal behavior of viscous dampers during short- and long-duration loads.